1997
DOI: 10.1007/s004360050303
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscope observations on Onchocerca ochengi and O. fasciata (Nematoda: Filarioidea)

Abstract: The fine structure of the females and males of Onchocerca ochengi (parasitizing zebu and cattle) and of the females of O. fasciata from camels were described and compared to other filariae of the genus Onchocerca. It was shown that O. ochengi resembles O. volvulus of humans in its degree of development, while being more primitive than O. gibsoni. Besides other similarities O. ochengi attracts inflammatory cells in the way of O. volvulus and these could be a model for chemotherapeutic trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…The description of the species 'Candidatus Wolbachia onchocercicola' is based on the studies reported by Determan et al [27], Egyed et al [31], Horeauf et al [46], Kozek and Marroquin [55], and Langworthy et al [59]. Cell size is 0.3 up to 0.8 m in diameter and 1.5 up to 1.8 m in length.…”
Section: Description Of 'Candidatus Wolbachia Onchocercicola'mentioning
confidence: 99%
“…The description of the species 'Candidatus Wolbachia onchocercicola' is based on the studies reported by Determan et al [27], Egyed et al [31], Horeauf et al [46], Kozek and Marroquin [55], and Langworthy et al [59]. Cell size is 0.3 up to 0.8 m in diameter and 1.5 up to 1.8 m in length.…”
Section: Description Of 'Candidatus Wolbachia Onchocercicola'mentioning
confidence: 99%
“…Despite the wide geographical distribution of onchocercosis in dromedaries, the biology of this parasite has not been studied in detail, including the insect vector species. A few studies have been performed on the histochemical distribution of several hydrolytic enzymes and dehydrogenases in adult O. fasciata [ 30 , 31 ] and fine structure of female specimens have been described using transmission electron microscope examination [ 13 ]. Similarly, the molecular characterization of filarial parasites of camel is scarce with only two publications including sequences of either O. fasciata [ 23 ] or D. evansi [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its pores may serve as conduits for nutrients from the lumen of the gill artery of the host to the hypodermis of the nematode. Pores within the cuticle were observed also in Onchocerca volvulus (Franz and Bu¨ttner 1983a;Determann et al 1997;Kozek and Figueroa-Marroquin 2002).…”
Section: Discussionmentioning
confidence: 91%
“…:Franz and Bu¨ttner 1983a;Determann et al 1997; Kozek and Figueroa-Marroquin 2002; Wuchereria bancrofti:Araujo et al 1995) the epicuticle is quite indistinct, but, probably, is lost during the procedure of fixation. The epicuticle apparently functions as a protection against inflammatory cells(Kozek and Figueroa-Marroquin 2002).…”
mentioning
confidence: 97%